A Radically Unfinished Dance: Contact Improvisation in a Time of Social Distance. Issue 1 (March 2021) - Goldman, Danielle
Abstract : Nancy Stark Smith passed away due to ovarian cancer on 1 May 2020. Her dedication to contact improvisation for nearly half a century—as a dancer, teacher, writer, and editor—contributed to its development and will continue to inform its ongoing vitality. But much remains uncertain for the future of contact improvisation. Complicated by the challenges of Covid-19, what sort of bodies will result from the practice going forward, and how might the form itself change?